Evolution of Sunna in Aqiqah Tradition of Kamang Mudiak Community Agam District West Sumatera - Eljambaky, Gusnanda; Ade, Irwansyah (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2024)
This article discusses the Kamang Mudiak community's reception of the Islamic teaching on the sunnah of akikah. The acceptance of the sunnah gave birth to the tradition of mambadakan paja. In this tradition, there is a process of transmission of the sunna that involves cultural agents. The discourse of contemporary hadith studies includes this study in the group of living hadith. This research uses a phenomenological approach. In analysing the materials, the author uses Fazlur Rahman's theory of sunna evolution (d. 1988) and Clifford Geertz's theory of symbolic interpretation (d. 2006). The results of this study reveal that the tradition of mambadakan paja was born evolutively. It has historical roots that go back to the tradition of welcoming the birth of a baby during the time of Muhammad. The formation of this tradition cannot be separated from the role of cultural agents such as ulama and ninik mamak. In its development, for the people of Kamang Mudiak this tradition is not only an Islamic identity but also a cultural identity. Through this tradition they give symbolic meaning as an expression of gratitude, prayer and hope and sacredness to something.